Comparison between Manual Lymph Drainage and Lymph stick on Circumference, Volume, Extracellular distribution ratio, Oxygen saturation, Body temperature and Satisfaction survey - Kim, Hyo-Jeong; Kim, Na-Young; Lee, Hye-Jeong; Lee, Dong-Yeop; Hong, Ji-Heon; Kim, Jin-Seop; Yu, Jae-Ho (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: This study investigated efficient interventional methods for reducing edema in women. Methods/Statistical analysis: 20 healthy adult women were participated in this study and directed to wear high heels. Then, three interventions were applied to them; long sitting, manual lymph drainage (MLD), lymph stick. This study measured the circumference, volume, extracellular distribution ratio, oxygen saturation, body temperature and satisfaction survey. Comparisons between each intervention were analyzed through one-way ANOVA and intragroup comparisons were used by T-test. Findings: The control group (long sitting) showed no significant difference in edema reduction. However, MLD and lymph stick showed significant differences (p<.05). In addition, there was no significant difference between the two interventions. According to the satisfaction survey, MLD and lymph stick showed a lot of positive answers on reducing edema, and lymph stick showed a lot of positive answers on overall satisfaction. In conclusion, we found the intervention that has a positive effect psychologically on the reduction of edema was lymph stick. Improvements/Applications: Because this study was limited to gender, age and adult women, we expect that a variety of study will be conducted for many kinds of patients in future.